Physical activity, sleep quality and daytime sleepiness among Ipoh young adults / Raja Ahmad Mustaqim Raja Ismail … [et al.] - Raja Ismail, Raja Ahmad Mustaqim; Syed Mud Puad, Sharifah Maimunah; Raja Hussain, Raja Nurul Jannat; Abu Kasim, Nurul Ain; Mazaulan, Mardiana; Mohamed, Muhamad Noor (Universiti Teknologi MARA, 2023)
Poor sleep quality due to physical inactivity and excessive use of gadgets is one of the issues faced by young adults. Unfortunately, there is limited data regarding sleep quality characteristics among young adults’ population in Malaysia. Therefore, this study aimed to investigate the relationship between physical activity, sleep quality, and daytime sleepiness among young adults in Ipoh. Total of three hundred thirty-five (N=335) young adults in Ipoh (male= 191, female= 144) age between 18-25 years old were participated in this study. Participants completed the International Physical Activity Questionnaires-Short Form (IPAQ-SF), Pittsburgh Sleep Quality Index (PSQI), and Epworth Sleepiness Scale (ESS). Results indicated that there was no significant correlation between physical activity and sleep quality (p>0.05) or between physical activity and daytime sleepiness (p>0.05). However, a significant correlation was found between sleep quality and daytime sleepiness (p<0.05, r= -0.278). The findings demonstrated that most of the variables in this study are not interdependent to each other except between sleep quality and daytime sleepiness. Objective measurement should be considered in future studies to provide additional insight into variables information.